2010
DOI: 10.1136/bmj.c810
|View full text |Cite
|
Sign up to set email alerts
|

Sex, health, and years of sexually active life gained due to good health: evidence from two US population based cross sectional surveys of ageing

Abstract: Objectives To examine the relation between health and several dimensions of sexuality and to estimate years of sexually active life across sex and health groups in middle aged and older adults. Design Cross sectional study. Setting Two samples representative of the US population: MIDUS (the national survey of midlife development in the United States, 1995-6) and NSHAP (the national social life, health and ageing project, 2005-6). Participants 3032 adults aged 25 to 74 (1561 women, 1471 men) from the midlife co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
285
5
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 410 publications
(333 citation statements)
references
References 39 publications
33
285
5
10
Order By: Relevance
“…Similar gender gaps have been reported elsewhere, 4,12 including by Chirinda and Zungu in this issue who estimate sexually active life expectancy in a cohort of older men and women in South Africa. In this study, women reported a markedly shorter sexually active life expectancy than men at the age of 50, with HIV having a negative impact on sexual activity only among women.…”
supporting
confidence: 85%
“…Similar gender gaps have been reported elsewhere, 4,12 including by Chirinda and Zungu in this issue who estimate sexually active life expectancy in a cohort of older men and women in South Africa. In this study, women reported a markedly shorter sexually active life expectancy than men at the age of 50, with HIV having a negative impact on sexual activity only among women.…”
supporting
confidence: 85%
“…Older adults who report good health are more likely to be sexually active, be sexually active for a longer duration (Lindau & Gavrilova, 2010), have more frequent sex, and experience higher sexual desire (Kontula & Haavio-Mannila, 2009). Similarly, being in a sexual partnership, -with frequent sexual expression, having a good quality sex life, and being interested in sex‖ (Syme, 2014, p. 36) has been positively associated with health among middle-aged and older adults.…”
Section: Introductionmentioning
confidence: 99%
“…However, health care providers often lack education concerning sexological issues, and their attitudes towards working to promote sexual health can be challenged by their own believed non-importance of sexual health for persons with disease or disability (Esmail, Darry, Walter, & Knupp, 2010;Low & Zubir, 2000). Sexual health is strongly related to feelings of well-being and general health (Field et al, 2013;Lindau & Gavrilova, 2010;Ratner, Erekson, Minkin, & Foran-Tuller, 2011), and previous research has shown that rehabilitation can promote sexual health (Kristina Areskoug- Josefsson & Gard, 2015;K. Areskoug-Josefsson & Oberg, 2009;Egan et al, 2013;Josefsson & Gard, 2012;Rosenbaum, 2006).…”
mentioning
confidence: 99%